Management of acute pseudomembranous candidiasis with angular cheilitis in diabetic patient - Winias, Saka; Hadi, Priyo; Prasetya, Shakira Garini; Sinaga, Angelica Joyce Yokhebeth (Institute of Computer Science (IOCS), 2025)
Diabetes mellitus (DM) is being increasingly documented even in developing countries. C. albicans infection is frequently found in diabetic patients. Diabetics and the ‘poorly controlled patients are considered as immunocompromised, though it is not easy to characterise the immunologic deficiencies clearly. Since infection is mostly preceded by colonization. The risk factors that increased the risk of Candida carriage in diabetic patients with DM were a higher age and a higher HbA1c level (poor regulation of DM). The purpose of this study is to report the management of Acute Pseudomembranous Candidiasis with Angular Cheilitis in diabetic patients. A 51-year-old lady complained of dryness and pain in the corner of the mouth, recurrence within 2 years after she had been diagnosed diabetic, which had worsened in the last two weeks. The corner of the mouth showed a fissure with reddish area. Oral mucosa showed multiple yellow-white pseudomembranous. The patient was prescribed antiseptic mouthwash and an antifungal oral suspension, which should be applied to the lesion 3-4 times daily. Ketoconazole, as a systemic antifungal, was given 200 mg/day. The laboratory test showed an increase in leucocytes cells count, monocytes, and ESR. A direct mycological examination and culture observation Candida albicans was performed. Referral to an internist to manage her systemic condition. This study concludes that immune dysfunctions in diabetics is contribute to the pathogenesis of Oral Candidiasis and Angular Cheilitis, which may lead to optimum treatment.